Antigen-Specific T-Cell Activation Independently of the MHC: Chimeric Antigen Receptor-Redirected T Cells - Abken, Hinrich; Chmielewski, Markus; Hombach, Andreas A. (Frontiers in Immunology, 2013)
Adoptive T cell therapy has recently shown powerful in initiating a lasting anti-tumor response with spectacular therapeutic success in some cases. Specific T cell therapy, however, is limited since a number of cancer cells are not recognized by T cells due to various mechanisms including the limited availability of tumor-specific T cells and deficiencies in antigen processing or major histocompatibility complex (MHC) expression of cancer cells. To make adoptive cell therapy applicable for the broad variety of cancer entities, patient's T cells are engineered ex vivo with pre-defined specificity by a recombinant chimeric antigen receptor (CAR) which consists in the extracellular part of an antibody-derived domain for binding with a tumor-associated antigen and in the intracellular part of a TCR-derived signaling moiety for T cell activation. The specificity of CAR mediated T cell recognition is defined by the antibody domain, is independent of MHC presentation and can be extended to any target for which an antibody is available. We discuss the advantages and limitations of MHC-independent T cell targeting by an engineered CAR and review most significant progress recently made in early stage clinical trials to treat cancer.